EVALUASI POSISI SEBAGIAN PAL BATAS KAWASAN HUTAN DENGAN TUJUAN KHUSUS PENDIDIKAN DAN PELATIHAN UNIVERSITAS LAMBUNG MANGKURAT - Dicky Ganesa; Suyanto Suyanto; Syam'ani Syam'ani (Jurnal Sylva Scienteae, 2024)
Re-evaluation of forest area boundaries is an important process in forest management that aims to ensure that the forest area boundaries determined are still relevant and in accordance with current conditions. Based on the results of boundary reconstruction, it shows that the location of the ULM Special Purpose Forest Area (KHDTK) boundary pal in the field does not follow natural boundaries such as foothills and ridges but in the middle of the hillside. This makes it difficult to ascertain the location of the boundary pal that can be known by field officers and the public. The purpose of this study was to analyze the results of the installation of KHDTK boundary pals (boundary reconstruction) against the characteristics of natural boundaries in the KHDTK area of Lambung Mangkurat University. This study used overlay method combined with field observation. The results of this study showed that at 76 coordinate points of the boundary pal position, there were findings that showed a discrepancy between the position of the boundary pal that had been set and the proper limit. Boundary Pal Position in Accordance with Predetermined Limits: Of the 76 coordinate points, there are only 8 boundary pal positions that correspond to the predetermined limit. A total of 49 pieces with an average distance difference of approximately 53.41 meters. Boundary pals are found outside the forest area and there are 19 boundary pals.Evaluasi ulang tata batas kawasan hutan adalah proses yang penting dalam pengelolaan hutan yang bertujuan untuk memastikan bahwa batas kawasan hutan yang ditetapkan masih relevan dan sesuai dengan kondisi terkini. Berdasarkan hasil rekontruksi batas menunjukan bahwa lokasi pal batas Kawasan Hutan Dengan Tujuan Khusus (KHDTK) ULM di lapangan tidak mengikuti batas alam seperti kaki bukit dan punggung bukit melainkan pada tengah lereng bukit.  Hal tersebut menyulitkan kepastian lokasi pal batas yang dapat dikenal oleh petugas lapangan maupun masyarakat. Tujuan penelitian ini adalah menganalisis hasil pemasangan pal batas KHDTK (Rekonstruksi batas) terhadap karakteristik batas alam di wilayah KHDTK Universitas Lambung Mangkurat. Penelitian ini menggunakan metode overlay dikombinasikan dengan  observasi lapangan. Hasil penelitian ini menunjukan bahwa pada 76 titik koordinat posisi pal batas, terdapat temuan yang menunjukkan adanya ketidaksesuaian antara posisi pal batas yang telah ditetapkan dengan batas yang semestinya. Posisi Pal Batas yang Sesuai dengan Batas yang Telah Ditentukan: Dari 76 titik koordinat, hanya terdapat 8 posisi pal batas yang sesuai dengan batas yang telah ditetapkan. Sebanyak 49 buah dengan rata-rata selisih jarak kurang lebih 53,41 meter. Pal batas ditemukan berada diluar kawasan hutan dan terdapat 19 buah pal batas.